Pengaruh Penerapan Pola Pengelolaan Keuangan Badan Layanan Umum (PK-BLU) Terhadap Kinerja Finansial, Kinerja Non Finansial Dan Mutu Layanan Pendidikan - Taupik Julia (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2016)
Thie Purposeof this study is to determine the effect of the application of financial management Public Service Agency (PK-BLU) to the performance of financial, non-financial performance and quality of education services. The independent variable in this study is the Financial Administration of the Public Service (PK- BLU), while the dependent variable is financial performance, non-financial performance and quality of education services. This research was conducted at the University of Sultan Ageng Tirtayasa by taking the 41 respondents to fill out the questionnaire. By using secondary data year period 2010-2014. The results showed that the application of the financial management of public service agencies (PK-BLU) has a positive effect to financial performance, non-financial performance and quality of education services.Keywords Financial management of public service agencies (PK-BLU), Financial Performance, non-financial performace, Quality of education  Service